Core competency scale for operating room nurses in China: Scale development, reliability and validity evaluation. Issue 6 (11th July 2021) - Mei, Na; Chang, Ling; Zhu, Zhonghai; Dong, Min; Zhang, Min; Zeng, Lingxia
Abstract: Aims: To develop a competency scale for operating room nurses and test its reliability and validity. Background: The existing Chinese Registered Nurse Competency Scale and the core competency scale for operating room nurses developed abroad cannot fully meet the capacity needs of Chinese operating room nurses. Methods: The scale was developed based on the results of qualitative interview and the Delphi method. Ten experts were selected for expert consultation, and 300 operating room nurses were recruited by convenience sampling for a cross‐sectional survey to test the reliability and validity of instrument.The reliability and validity of the scale was assessed based on internal consistency reliability, test–retest reliability and confirmatory factor analysis. Data collection was conducted between March to July, 2015. Results: An initial scale with 42 items was confirmed, and 36 items remained. The internal consistency Cronbach's α was 0.97 for the overall scale and 0.88–0.94 for the subscales. The retest reliability ranged from 0.55–0.96. Five factors were extracted by exploratory factor analysis, and they explained 66% of the total variance. The fitting indices of the confirmatory factor analysis were as follows: χ2/df  = 3.47, CFI = 0.83, TLI = 0.81, SRMR = 0.06 and RMSEA = 0.09. Conclusions: The core competency scale for operating room nurses with 5 components and 36 items had acceptable reliability and validity. The scale could continue to be optimized in the future.